口腔癌の再発を減らす切除の工夫−舌リンパ節への対応 - 吉田, 遼司; 中山, 秀樹; 井上, 淳貴 (日本口腔外科学会雑誌, 2024)
The lingual lymph node (LLN) metastasis is not included in the cervical lymph node level system in oral cancer. Although the frequency of LLN metastasis is relatively low, we should always take into consideration that it is often difficult to treat once it occurs. In this review, we investigated LLN metastasis in patients with oral squamous cell carcinoma (OSCC), including the para-hyoid region. The subjects were 311 patients with OSCC at the tongue and oral floor who were treated between January 2012 and December 2019. LLNs were classified based on the reports of Suzuki et al. (Head and Neck Surgery, 2016). The analysis showed that LLN metastases were found in 10 patients (3.2％). Lateral LLNs and para-hyoid LLNs were found in 5 cases and 5 cases, respectively. The primary site of metastatic lesions were the tongue in 8 cases and on the floor of the mouth in 2 cases. One case of metastasis in the lateral LLN was identified at the time of initial treatment, four cases were identified as delayed neck metastasis after partialglossectomy, and one case was identified as neck recurrence after neck dissection. All cases of para-hyoid LLNs were identified as neck recurrences after initial radical surgery. The cases of LLN metastasis were extremely poor regardless of multimodality treatment. LLN metastases are often difficult to control if the opportunity for treatment is missed, and their presence needs to be recognized during treatment.